Prevalence of selective immunoglobulin A deficiency in healthy Turkish school children - Baştürk, Bilkay; Sarı, Sinan; Aral, Arzu; Dalgıç, Buket (The Turkish Journal of Pediatrics, 2011)
Immunoglobulin A (IgA) deficiency is the most common primary deficiency. We aimed to define the prevalence of IgA deficiency among healthy school children in Turkey and the differences between geographical regions. Blood samples were collected from 20,331 healthy school children from all regions across Turkey. The serum IgA levels were tested through nephelometric method, and all 108 samples with IgA levels lower than 5 g/L were tested through ELISA for IgG and IgM levels. All IgG and IgM values were within the normal range in all cases, and no concomitant deficiency was observed. Our study results showed that the selective IgA deficiency incidence was 0.52% (1:188). The highest incidence, of 1:128.7, was observed in children from the Marmara region; the Black Sea Region levels (1:132.7) were lower, and the Mediterranean levels (1:365.7) were the lowest.